A study about the combination of Awan Larat motif and graffiti in Malaysia / Mohamad Azhari Mohd Pauzi - Mohd Pauzi, Mohamad Azhari (2014)
Graffiti is writing or drawings scribbled, scratched, or sprayed illicitly on a wall or other surface in a public place. Motif which is used in Malay art decoration can also be applicable in designing of motif for Graffiti. The impact of using the motif can be determined by the demand and needs of the individual. This study want to show that the effectiveness and potential of the motif for our local culture identity. The investigation is to look into the suitability of the Awan Larat motif in the decoration of the Graffiti design. A strong sense of belonging towards dignifying the culture identity. Besides that, this research has been carried out in the systematic manner which is come out with literature review, preparation for the questionnaires and interview respondents. The usage of the Malay motif applied on Graffiti never been used. So that our Malay motif have potential and prestige to introduce in international. The design concept of graffiti that are combined with awan larat can described our originality of culture identity to the western influence.